A Study of Trends in Buying Pattern of Smartphones in India - Dagar, Sanchit; Khan, Asma (Journal of Commerce and Trade, 2018)
The rapidly growing demand of Smartphone has created a buzz around the world. Nowadays, most of the consumers opt to have a Smartphone. The increasing innovation in mobile phone industries has brought this craze among the people on Smartphone. India has witnessed a dramatic growth in the number of mobile phone users in the recent past. Equally impressive has been the increase in internet access. Although mobiles allow us to stay connected, it is the convergence of internet access and smartphones that has resulted in tectonic shifts in consumer awareness, outlook and behaviour. Smartphone is configured by an operating system with advanced computing capability and connectivity. Generally Smartphone has high sensor big touch screens and high pixel cameras with lots of features and applications. Mostly people use applications for internet browsing, email, navigation, social media, listening music, reading news, games, finance, health and fitness, taking notes, calendar, weather forecast and lots of other things. These features and applications in Smartphone somehow have made people's life easier either in daily life, at work or for entertainment purpose. As a result, the market of Smartphone has been escalating every year with increasing innovations. Classification-JEL : L11, L25, L96